Distribution of leaf characteristics in relation to orientation within the canopy of woody species - Escudero, Alfonso; Fernández, José; Cordero, Angel; Mediavilla, Sonia (Acta Oecologica, 2013)
Over the last few decades considerable effort has been devoted to research of leaf adaptations to environmental conditions. Many studies have reported strong differences in leaf mass per unit area (LMA) within a single tree depending on the photosynthetic photon flux density (PPFD) incident on different locations in the crown. There are fewer studies, however, of the effects of differences in the timing of light incidence during the day on different crown orientations. Leaves from isolated trees of Quercus suber and Quercus ilex in a cold Mediterranean climate were sampled to analyze differences in LMA and other leaf traits among different crown orientations. Gas-exchange rates, leaf water potentials, leaf temperatures and PPFD incident on leaf surfaces in different crown orientations were also measured throughout one entire summer day for each species. Mean daily PPFD values were similar for the leaves from the eastern and western sides of the canopy. On the western side, PPFD reached maximum values during the afternoon. Maximum leaf temperatures were approximately 10–20% higher on the west side, whereas minimum leaf water potentials were between 10 and 24% higher on the east side. Maximum transpiration rates were approximately 22% greater on the west, because of the greater leaf-to-air vapor pressure deficits (LAVPD). Mean individual leaf area was around 10% larger on the east than on the west side of the trees. In contrast, there were no significant differences in LMA between east and west sides of the crown. Contrary to our expectations, more severe water stress on the west side did not result in increases in LMA, although it was associated with lower individual leaf area. We conclude that increases in LMA measured by other authors along gradients of water stress would be due to differences in light intensity between dry and humid sites.
Keywords: Canopy orientation; leaf morphology; Leaf temperature; Quercus; water potential